MULTIDIMENSIONAL TREATMENT OF ENDOMETRIOSIS – THE ROLE OF NUTRITIONAL, PHYSIOTHERAPEUTIC AND PSYCHOLOGICAL INTERVENTIONS - Barbara Teresińska,; Michał Lenart,; Wojciech Gąska,; Ignacy Rożek,; Izabela Lekan,; Joanna Mazurek,; Agnieszka Brzezińska,; Weronika Tuszyńska,; Alicja Sodolska,; Barbara Madoń, (International Journal of Innovative Technologies in Social Science, 2025)
Endometriosis is a chronic, progressive gynecological disease characterized by the presence of active endometrial tissue outside the uterine cavity. Endometriosis impacts around 10% of women in their reproductive years, often leading to persistent pain, cycle disturbances, and challenges with conception. Conventional management, which includes medication and surgery, is often insufficient due to high recurrence rates and suboptimal outcomes, prompting increased focus on complementary treatment strategies.The main aim of this work is to analyze the role of three key areas of supportive therapy: diet, physiotherapy and psychotherapy in relieving the symptoms of endometriosis and improving the quality of life of patients. This is a review-based study that analyzes scientific sources from 1997 to 2025. Analysis of current studies highlights the potential of an anti-inflammatory diet, regular pelvic-focused physiotherapy, and psychotherapy as effective complementary strategies alongside conventional treatment. An integrated therapeutic approach, taking into account the somatic and psychological needs of patients, seems to be crucial in the effective management of endometriosis.